The Relationship Between Dietary Patterns, Medical History, And Mbg Administration With The Nutritional Status Of Preschool Children In The Working Area Of Cibodas Health Center In 2025 - Fathia Rizki; Meita Dhamayanti; Syifa Maharani (International Journal of Health Engineering and Technology, 2026)
Nutritional problems in preschool children remain a serious concern in Indonesia, with a national stunting prevalence of 21.6%. Although the rate is lower in the working area of the Cibodas Community Health Center, cases of double burden of malnutrition (underweight and overweight) are still present. This study aimed to examine the relationship between dietary patterns, medical history, and participation in the Free Nutritious Meal Program (MBG) with the nutritional status of preschool children. A quantitative cross-sectional design was used, involving 92 preschool children selected through purposive sampling. Data were collected using dietary pattern and medical history questionnaires, along with anthropometric measurements, and analyzed using the Chi-Square test. The majority of children had good dietary patterns (52.2%), most had a history of illness (62.0%), and more than half participated in the MBG program (56.5%). Nutritional status was dominated by normal nutrition (73.9%), followed by undernutrition (14.1%) and overnutrition (12.0%). Bivariate analysis indicated significant associations between dietary patterns (p=0.000), medical history (p=0.000), and MBG participation (p=0.000) with nutritional status. These three factors are important determinants of preschool children’s nutritional status, suggesting that nutrition improvement efforts should focus on enhancing dietary patterns, preventing illness, and optimizing MBG program coverage.